Detection of porcine DNA in commercially processed meat products sold in Sarawak - Sajali, Nurhayatie (IIUM Press, 2022)
Porcine DNA authentication in commercial products is critical due to improper or non-certified Halal logo on its packaging. This study detected the presence of porcine DNA in particularly processed meat products sold in Sarawak. A total of 75 samples were collected, consisting of poultry, beef, and seafood products. DNA was isolated and amplified in a polymerase chain reaction that targeted cytochrome B (cytb) and mitochondrial D-loop. PCR products were analysed via gel electrophoresis and viewed through gel documentation. The positive result was observed in 5 samples: 3 from poultry and 2 from beef. The DNA band were detected at an amplicon size of 174 base pairs for poultry products whereas 100 base pairs for beef products. Porcine DNA was absent in seafood products. Positive samples were validated through DNA sequencing. Nucleotide sequences from DNA sequencing were compared with the database using the Basic Local Alignment Search Tool (BLAST). BLAST analysis indicated percentages ranging from 96.83% to 100%, demonstrating high similarity with porcine DNA; one of the samples was labelled with a foreign Halal logo. In summary, this study provides the groundwork for further inspection of the Halal status in commercially processed meat products available in Sarawak.